Meta-analysis of dengue severity during infection by different dengue virus serotypes in primary and secondary infections - Soo, Kuan Meng; Khalid, Bahariah; Ching, Siew Mooi; Chee, Hui Yee (Public Library of Science, 2016)
Introduction: Dengue virus (DENV) infection is currently a major cause of morbidity and mortality in the world; it has become more common and virulent over the past half-century and has gained much attention. Thus, this review compared the percentage of severe cases of both primary and secondary infections with different serotypes of dengue virus. Methods: Data related to the number of cases involving dengue fever (DF), dengue hemorrhagic fever (DHF), dengue shock syndrome (DSS) or severe dengue infections caused by different serotypes of dengue virus were obtained by using the SCOPUS, the PUBMED and the OVID search engines with the keywords “(dengue* OR dengue virus*) AND (severe dengue* OR severity of illness index* OR severity* OR DF* OR DHF* OR DSS*) AND (serotypes* OR serogroup*)”, according to the MESH terms suggested by PUBMED and OVID. Results: Approximately 31 studies encompassing 15,741 cases reporting on the dengue serotypes together with their severity were obtained, and meta-analysis was carried out to analyze the data. This study found that DENV-3 from the Southeast Asia (SEA) region displayed the greatest percentage of severe cases in primary infection (95% confidence interval (CI), 31.22–53.67, 9 studies, n = 598, I2 = 71.53%), whereas DENV-2, DENV-3, and DENV-4 from the SEA region, as well as DENV-2 and DENV-3 from non-SEA regions, exhibited the greatest percentage of severe cases in secondary infection (95% CI, 11.64–80.89, 4–14 studies, n = 668–3,149, I2 = 14.77–96.20%). Moreover, DENV-2 and DENV-4 from the SEA region had been found to be more highly associated with dengue shock syndrome (DSS) (95% CI, 10.47–40.24, 5–8 studies, n = 642–2,530, I2 = 76.93–97.70%), while DENV-3 and DENV-4 from the SEA region were found to be more highly associated with dengue hemorrhagic fever (DHF) (95% CI, 31.86–54.58, 9 studies, n = 674–2,278, I2 = 55.74–88.47%), according to the 1997 WHO dengue classification. Finally, DENV-2 and DENV-4 from the SEA region were discovered to be more highly associated with secondary infection compared to other serotypes (95% CI, 72.01–96.32, 9–12 studies, n = 671–2,863, I2 = 25.01–96.75%). Conclusion: This study provides evidence that the presence of certain serotypes, including primary infection with DENV-3 from the SEA region and secondary infection with DENV-2, DENV-3, and DENV-4 also from the SEA region, as well as DENV-2 and DENV-3 from non SEA regions, increased the risk of severe dengue infections. Thus, these serotypes are worthy of special consideration when making clinical predictions upon the severity of the infection.